Respuesta :
Answer:
8x^4+9x^3+4x-1
Step-by-step explanation:
(6x^3 – 5x^2 + 3x – 5) + (8x^4 + 3x^3 + 5x^2 + x + 4)
Group like terms
8x^4+6x^3+3x^3-5x^2+5x^2+3x+x-5+4
8x^4+9x^3+4x-1
Answer:
[tex]\left(6x^3-5x^2+3x-5\right)+\left(8x^4+3x^3+5x^2+x+4\right)[/tex]
Combine like terms
[tex]=8x^4+6x^3+3x^3-5x^2+5x^2+3x+x-5+4[/tex]
Add: -5x²+5x²=0
[tex]=8x^4+6x^3+3x^3+3x+x-5+4[/tex]
Now add 6x³+3x³=9x³
[tex]=8x^4+9x^3+3x+x-5+4[/tex]
Add like terms 3x +x=4x
[tex]=8x^4+9x^3+4x-5+4[/tex]
Now add -5+4=-1
[tex]=8x^4+9x^3+4x-1[/tex]
OAmalOHopeO